Typology of companies networks for competitive assessment: an application in higher education institutions - Zaneti, Gislaine Barbosa [UNESP]; Rocha, Regina Ferreira da [UNESP]; Fusco, José Paulo Alves [UNESP]; Rodrigues, José de Souza [UNESP] (My University, 2014)
Taking into account the changes in the market scenario by virtue of globalization, Institutes of Higher Education (IES) as well as other organizations seek their competitive stability. For that reason, it is up to organizations to adopt innovative models of management for their operations aimed at improving results. Company networks consist of a model that is perfect for uniting efforts through cooperation among partners in a given business, which can involve ties of different natures. This paper shows the development and the application of an auxiliary technique to analyze the intensity, nature and importance of internal and external relations in the formation of results for a company network. For such, a multiple case study was conducted at two IES in the State of São Paulo and their networks of partners and employees in order to observe their specificities and organizational strategies. The study demonstrated the existence of specific performance criteria (pillars) for each IES and its network, resulting from its competitive reality. It reveals evidence that the education pillar is strengthened in both cases, and the research pillar is growing, although it is the weakest. The outreach pillar is the most robust in the public IES and the financial sustainability pillar is relevant for the private IES, and it was only detected in this IES.
Keywords: Intercompany networks; Institution of Higher Education; Network Typology; Intensity of relations; Nature of relations